2023
DOI: 10.3390/rs15030573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the IMERG Early-Run Precipitation Estimates over South American Country of Chile

Abstract: Accurate rainfall measurement is a challenge, especially in regions with diverse climates and complex topography. Thus, knowledge of precipitation patterns requires observational networks with a very high spatial and temporal resolution, which is very difficult to construct in remote areas with complex geological features such as desert areas and mountains, particularly in countries with high topographical variability such as Chile. This study evaluated the performance of the near-real-time Integrated Multi-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Thus, IMERG can improve precipitation estimations in zones of high elevations. Consistently, da Silva et al (2023) reported that IMERG achieves a lower incidence of error than other satellite products for regions situated at elevations beneath 2000 m.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Thus, IMERG can improve precipitation estimations in zones of high elevations. Consistently, da Silva et al (2023) reported that IMERG achieves a lower incidence of error than other satellite products for regions situated at elevations beneath 2000 m.…”
Section: Resultssupporting
confidence: 55%
“…In this regard, several studies have compared and evaluated the accuracy of different satellite products using data from ground‐based measurement stations as reference in different regions of South America. The satellite products previously studied include the Tropical Rainfall Measuring Mission (TRMM; Silva Lelis et al, 2018; Vila et al, 2009), Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS; Cerón et al, 2020), the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN; de Goncalves et al, 2006; Derin et al, 2016; Hsu et al, 1997), different products of the Integrated Multi‐satellite Retrievals for Global Precipitation Measurements (IMERG; da Silva et al, 2023; Gadelha et al, 2019; Getirana et al, 2020; Pradhan et al, 2022; Rodrigues et al, 2021; Rozante et al, 2018), and a combination of several satellite products (Baez‐Villanueva et al, 2018; Hobouchian et al, 2012; Palharini et al, 2020). In general, satellite products reproduce precipitation with different biases over South America.…”
Section: Introductionmentioning
confidence: 99%
“…These three processing stages cater to the diverse needs of different data users. However, the accuracy of the inversion process in IMERG has been a subject of interest for numerous researchers [3], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%